A Contribution to the Study of Grounding Systems Based on Circuit Synthesis - de Seixas, Claudiner Mendes; Kurokawa, Sérgio [UNESP] (Springer Nature, 2018)
This work presents an unprecedented technique capable of representing grounding grids directly in the time domain using an association of passive and discrete circuit elements (RLC circuits: resistors, inductors and capacitors). It is based on the frequency response of RLC circuits and ensures that all elements will be positive (physically implementable), solving situations that other techniques, such as vector fitting, generally presented in the literature are not able to solve using only passive circuits (feasible). The proposed technique is applied from the harmonic impedance previously provided, and therefore this impedance can be obtained using any model. It is accurate; it presents excellent results and was validated by comparing the harmonic admittance and transient voltage curves to those obtained with the hybrid electromagnetic model. The advantage of this technique is that it allows that several components in power systems, such as grounding systems and transmission towers, to be represented by a feasible circuit. Once this circuit is implemented in the laboratory, analysis and comparisons with conventional software (e.g. ATP) can be made and accurate transient electromagnetic responses can be obtained.
Keywords: Electromagnetic transients; Frequency response; Grounding systems; Impedance; Lightning stroke; Time domain